Development of a non-inductive high voltage D-Dot probe voltage transducer system - Abd. Malek, Zulkurnain (Universiti Teknologi Malaysia, 2007)
has been directed towards the characterisation of the electrical behaviour of the material under various stress conditions. There is now an extensive published literature on the response of the material to impulse current stresses of different shape and amplitude. An aim of some of these investigations is to achieve an equivalent circuit representation which adequately simulate the observed test results. An adequate equivalent circuit representation will aid the reliable and efficient design of the overvoltage protection and help to improve the optimisation of the protective devices. A significant impediment to the accurate characterisation of zinc oxide has been the lack of reliable test data especially for fast-rate-of-rise impulses in the microsecond and sub-microsecond range. The measurement of residual voltages using impulses in this range is highly influenced by the circuit arrangement and measurement transducer characteristics. The measurement of voltage using parallel connected transducers is inherently affected by circuit inductances and the transfer characteristic of the divider itself. An improved voltage transducer based upon the D-dot probe principle was adopted. Previous published results obtained using this transducer showed that there is no evidence to link the voltage overshoot seen on the residual voltage trace of zinc oxide with the characteristics of the material itself. This observation has positive implications for the protective performance of zinc oxide and will allow a more accurate characterisation of the material.